Las artes escénicas en Quito: análisis de las condiciones de producción de espectáculos independientes - Campos Naranjo, Santiago Javier (2019)
The current research describes the production conditions of scenic art spectacles generated by independent producer cores from Quito. With this regard, it uses as reference two reports published by the Minister of Culture and Heritage of Ecuador: the first one called “Caracterización de los sectores de las Industrias Culturales (Dirección de información del Sistema Nacional de Cultura, 2018)”, which analyses the situation of cultural ventures of artistic areas; and the second one, entitled “Las artes vivas y escénicas en Ecuador (SIIC, 2018)” which describes specifically the labour and economic features of this sector. In order to contrast these references, the author conducted a survey to artists and cultural promoters. The survey shows a closer approach to the producers and assesses the incidence of public policies. Furthermore, this addresses approaches issues such as the linking of the performing arts to the cultural or creative industries, the funding sources of the producer cores, the contributions of the sector to the economy of the country, and the role of the State in the promotion of the arts.